Deep Searches for Radio Pulsations and Bursts from Four Magnetar and a Magnetar-like Pulsar with FAST - Juntao Bai; Na Wang; Shi Dai; Shuangqiang Wang; Jianping Yuan; Wenming Yan; Lunhua Shang; Xin Xu; Shijun Dang; Zhen Zhang (The Astrophysical Journal)
We report on radio observations of four magnetars SGR 0501+4516, Swift 1834.9–0846, 1E 1841–045, SGR 1900+14, and a magnetar-like pulsar PSR J1846–0258 with the Five-hundred-meter Aperture Spherical radio Telescope at 1250 MHz. Notably, PSR J1846–0258 was observed 1 month after its 2020 X-ray outburst. The data from these observations were searched for periodic emissions and single pulses. No radio emission was detected for any of our targets. After accounting for the effect of red noise, the nondetections yield stringent upper limits on the radio flux density, with S _1250 ≤ 16.9 μ Jy for the four magnetars and the magnetar-like pulsar, along with constraints on single-pulse flux densities. Our deep radio observations suggest that these magnetars and the magnetar-like pulsar are indeed radio-quiet sources or unfavorably beamed. The resulting flux upper limits, along with previous findings, are discussed, highlighting the significance of further radio observations of radio-quiet magnetars and the high-B magnetar-like pulsar.